Peran Filsafat Pendidikan Islam dalam Pembentukan Karakter dan Identitas Peserta Didik: Analisis Konseptual dan Praktis - Nia Ramadhani; Nur Ikhsaniyah Lubis; Herlini Puspika Sari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Islamic educational philosophy plays a crucial role in forming the character and identity of students through integrating Islamic teaching values into the educational process. The problem with this study is the less than optimal application of Islamic values in the modern education system, which has an impact on the weak character and identity of students. The formation of character and identity in the context of Islamic education requires a balance between cognitive, affective and psychomotor aspects based on the teachings of monotheism, morals and the concept of humans as caliphs on earth. The aim of this research is to analyze conceptually and practically the role of Islamic educational philosophy in forming students who have noble character and have a strong Islamic identity. This research methodology uses a qualitative approach with in-depth literature analysis. Data was obtained through a literature review of primary and secondary literature related to Islamic educational philosophy, character formation and identity from an Islamic perspective. A concept analysis approach is used to explore the relationship between the principles of Islamic educational philosophy and educational goals which are directed at the formation of complete humans (insan kamil). The results of this research show that the consistent application of Islamic educational philosophy can be a solution in dealing with identity crises and moral degradation in students as well as a solid foundation in creating a generation that has a balance between science and Islamic values. Abstrak Filsafat pendidikan Islam memainkan peran krusial dalam pembentukan karakter dan identitas peserta didik melalui pengintegrasian nilai ajaran Islam ke dalam proses pendidikan. Masalah dari kajian ini adalah kurang optimalnya penerapan nilai-nilai Islam dalam sistem pendidikan modern, yang berdampak pada lemahnya karakter dan identitas peserta didik. Pembentukan karakter dan identitas dalam konteks pendidikan Islam menuntut ada kesetaraan antar unsur afektif, kognitif serta psikomotorik yang berbasis pada ajaran tauhid, akhlak, dan konsep manusia sebagai khalifah di bumi. Maksud dari riset ini ialah agar menganalisa secara konseptual dan praktis peran filsafat pendidikan Islam untuk menciptakan murid yang mempunyai akhlak baik serta memiliki identitas keislaman yang kuat. Metodologi riset ini menggunakan pendekatan kualitatif memakai analisa literatur yang mendalam. Data diperoleh melalui kajian pustaka dari literatur primer serta sekunder yang berkaitan pada filsafat pendidikan Islam, pembentukan identitas, serta identitas pada perspektif Islam. Pendekatan analisis konsep digunakan untuk menggali keterkaitan antara prinsip-prinsip filsafat pendidikan Islam dengan tujuan pendidikan yang diarahkan pada pembentukan manusia paripurna (insan kamil). Hasil riset ini memperlihatkan bahwa penerapan filsafat pendidikan Islam yang konsisten bisa jadi solusi dalam menghadapi krisis identitas dan degradasi moral pada peserta didik serta sebagai landasan yang kokoh dalam menciptakan generasi yang memiliki keseimbangan antara ilmu pengetahuan dan nilai-nilai keislaman.